Berpikir Positif dan Rasa Bersyukur terhadap Resiliensi Diri (Studi Pada Karyawan yang terkena PHK di Masa Pandemi Covid-19): Dela Aulia, Amira Nurul Rezeki, Nurul Syamsiyah, Wustari L Mangundjaya - Aulia, Dela; Nurul Rezeki, Amira; Syamsiyah, Nurul; L Mangundjaya, Wustari (Fakultas Psikologi Universitas Bhayangkara Jakarta Raya, 2023)
The Covid-19 pandemic period caused several consequences, namely many companies experienced an economic downturn, so they chose to terminate their employment (PHK). The purpose of this study was to determine the relationship between positive thinking and gratitude with resilience in employees affected by layoffs, especially working men and to find out how to develop resilience to victims of layoffs. The method uses a quantitative correlational approach. Data were collected through 3 kinds of questionnaires, namely positive thinking, gratitude, and self-resilience. Respondents were 99 people who came from the South Tambun area experienced termination of employment at the company due to the economic downturn in the company. The data were analyzed through the correlational method. The results showed that there was a positive and significant relationship between positive thinking and gratitude and self-resilience. Furthermore, the results of the study show that positive thinking has a greater correlation value than gratitude.